Novos materiais de Saturnalia tupiniquim (Dinosauria: sauropodomorpha) e suas implicações para o entendimento da variação intraespecífica nos primeiros dinossauros - Damke, Lísie Vitória Soares (2024)
A unique moment in the evolutionary history of dinosaurs has been witnessed by Triassic rocks from southern Brazil. From these rocks, together with that from Argentina and Zimbabwe, the oldest dinosaurs have been unearthed. Among them, the sauropodomorphs are the most abundant and diverse. These animals were relatively gracile and bipedal, differing significatively from their ‘successors’, the sauropods. Over the last three decades, our understanding regarding these animals has increased in response to the description of new species. During a fieldwork in 2018, a new material assigned to a sauropodomorph was excavated. The specimen comprises the main theme of this master’s dissertation, which aims to identify, describe, and investigate the implications from this material. UFSM 11660 was mechanically prepared, allowing the recognition of cranial, axial, pelvic, and hindlimb elements of at least three individuals. The taxonomic assignment was performed according to first-hand comparisons, as well as it was supplied with phylogenetic and disparity analyses. The first phylogenetic analyses placed UFSM 11660 within Saturnaliidae. In the second phylogenetic analysis, the specimen nests together with the type-series of Saturnalia tupiniquim. In the morphospace analysis, UFSM 11660 was found close to S. tupiniquim and its position differs significantly from Eoraptor lunensis and Buriolestes schultzi. Therefore, UFSM 11660 is assigned to S. tupiniquim and reveals new data for the species, especially regarding the rostral portion. It was possible to conclude that the rostrum of S. tupiniquim was proportionally shorter than that of other coeval sauropodomorphs. Yet, we also discuss some characters related to intraspecific variation within S. tupiniquim.